Identification of Garlic Viruses Associated with Seed Bulbs and Consumption Bulbs from Several Locations in Indonesia - Nurulita, Sari; Mawarni, Sofi; Hidayat, Sri Hendrastuti (HAYATI Journal of Biosciences, 2024)
Virus infection is one of the major constraints in garlic production since the viruses are readily accumulated on vegetative propagation material (bulbs). This research aimed to detect garlic common latent virus (GCLV), shallot latent virus (SLV), onion yellow dwarf virus (OYDV), and leek yellow stripe virus (LYSV) infecting local garlic as seed bulb and imported garlic as consumption bulb. Seed bulb samples were obtained from seed breeders in several garlic growing centers in Indonesia. In contrast, consumption bulb samples were obtained from plant quarantine warehouses and three local markets in Bogor. Some bulb samples were used for morphological observations, and some were germinated in the laboratory until the leaves emerged. Leaves were collected for virus detection by RT-PCR using specific primers for GCLV, SLV, OYDV, and LYSV. Seed and consumption bulbs have differences in their morphological characteristics, especially in the type of neck hardness and the size of the bulb diameter. OYDV and LYSV infections were successfully detected in seed and consumption bulbs, while SLV was only found in consumption bulbs. Nucleotide sequence analysis showed that SLV from consumption bulbs formed one group, GCLV from seed bulbs formed one group, while OYDV and LYSV from seed and consumption bulbs were in different groups, indicating that the viruses came from different strains. Further research through high-throughput detection methods and providing virus-free planting material are needed to anticipate the spread of new strains of garlic viruses in Indonesia.